Effectiveness of exercise countermeasures for the prevention of musculoskeletal deconditioning in simulated hypogravity: A systematic review. (August 2021) - Swain, P.; Laws, J.M.; De Martino, E.; Wotring, V.; Caplan, N.; Winnard, A.
Abstract: Background: Exercise countermeasures are the main approach taken to protect astronauts from musculoskeletal deconditioning in microgravity (μg). Future exploration class missions will require astronauts to live on the surface of the Moon (0.16g) and Mars (0.38g) in hypogravity where the level of protection is assumed to be insufficient. However, it is not well understood how much exercise is required to protect the musculoskeletal system against 'small planet deconditioning'. The purpose of this review was to systematically synthesize evidence regarding the effectiveness of exercise countermeasures for the prevention of musculoskeletal deconditioning in hypogravity. Method: Databases were searched for relevant literature using appropriate search terms: PubMed, Web of Science, EMBASE, The Cochrane Collaboration Library, SPORTDiscus, the National Aeronautics and Space Administration (NASA) Technical Reports Sever, the NASA Life Science Data Archive and the German Aerospace Centre Elibrary. Two independent reviewers screened hits for relevance in accordance with the a priori PICOS criteria. Studies that included Earth based hypogravity analogs (e.g. head up tilt bed rest), a healthy terrestrial population, an exercise countermeasure and non exercise control group (i.e. randomized/clinical control trial), measuring any musculoskeletal outcome, were eligible for inclusion. Space related research (e.g. Lunar mission data) were not eligible for inclusion. Results: No studies were identified that met the eligibility criteria established for this review. Of the n = 2805 articles identified, n = 124 were classified as potentially relevant, however all were excluded following full text examination. Conclusions: Assumptions regarding the effect of hypogravity on the human musculoskeletal system are yet to be confirmed with long duration data. Future research should aim to fill this gap by investigating the longitudinal effects of simulated hypogravity (and Lunar/Martian habitat environments) on the human musculoskeletal system, to establish whether any deconditioning is of a large enough magnitude to compromise health and performance. If so, thereafter investigating exercise countermeasure strategies to prevent deconditioning in simulated Lunar/Martian settings will help inform evidence-based medical guidelines for planetary exploration. The ecological validity and thus transferability of data from chronic hypogravity analogs are essential to providing accurate and high quality data. Therefore, Lunar/Martian data is extremely valuable to understand whether data collected in analogs can be accurately transferred. Highlights: Review of exercise to prevent musculoskeletal deconditioning in hypogravity. Zero studies met the eligibility criteria. Long duration animal and human research is required in simulated hypogravity.